Refugee news, refugee politics : journalism, public opinion and policymaking in Europe - Dell'Orto, Giovanna Ed; Wetzstein, Irmgard Ed (Routledge, 2019)
The unprecedented arrival of more than a million refugees, asylum seekers, and migrants – plus the political, public, and policy reactions to it – is redefining Europe. The repercussions will last for generations on such central issues as security, national identity, human rights, and the very structure of liberal democracies. What is the role of the news media in telling the story of the 2010s refugee crisis at a time of deepening crisis for journalism, as “fake news” ran rampant amid an increasingly distrustful public?